Investment Behaviour and Biases of Investor: An Analytical Review of Bihar - Sah, Santosh (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
In recent times, capital markets are attracting the attention of retail investors across the globe and this number is increasing due to diversified reasons like declining interest rates, insecurity and volatility amongst fixed income securities, increasing awareness about investment options, trading through the proper means, increasing role of technology in capital markets and their tech savvy investors etc. However, to understand this whole process, behavioural finance acts as a catalyst and helps us as a medium both for reasons and causes for those reasons. Behavioural finance refers to the psychology of finance and people dealing in finance. This subject contributes and affects finance in multiple ways as it evaluates human desire and the motivating factors of desire in making investment, there by contributing to value maximization of investments made. It is an interdisciplinary subject with flavours of psychology, economics and sociology. The purpose of this paper is to develop a conceptual understanding and presenting a framework in the field of behavior finance & biases. The paper has drawn outline of theory as well as practical implication in the field i.e. financial decision- making process and the factors affecting the behavior. Keywords: Behavior finance, Behavior biases, investment, Efficient market hypothesis, Financial decision making process, Prospect theory